Vitamin C content of naturally produced fresh vegetables in Kalasin Province, Thailand - Theeranat Suwanaruang; Tunwa Chaiteing (Caspian Journal of Environmental Sciences)
The purpose of this study was to ascertain the vitamin C content of locally cultivated vegetables in Thailand. As the study's sample veggies, local, conveniently accessible product is regularly consumed by Thais. Vegetables include eggplant, Solanum melongena L., kajon flowers, Telosma minor Craib, lettuce, Lactuca sativa L., butterfly pea flowers, Clitoria ternatea Linn, acacia. Acacia farnesiana (L.) Willd, spinach. Spinacia oleracea L., and zucchini, Cucurbita L. var. cylindica Pans. Fresh vegetable vitamin C levels range from 130 ±1.00 mg kg-1, 340 ± 0.58 mg kg-1, 350 ± 1.00 mg kg-1, 340 ± 0.58 mg kg-1, 440 ± 0.58 mg kg-1, 490 ± 0.58 mg kg-1 and 140 ± 0.58 mg kg-1, respectively. Spinach contained the most vitamin C, with a concentration of 490 mg kg-1 followed by Acacia, lettuce, kajon flowers, butterfly pea flowers and zucchini respectively. However, vitamin C is still necessary for healthy skin and a strong immune system. The body can also get the appropriate daily quantity of vitamin C by eating the right kinds and amounts of fruits and vegetables.